Treatment Minimization in Older Patients With Early-Stage Breast Cancer. Issue 4 (July 2017) - Hansen, Tara M.; Zellars, Richard C.
Abstract : Abstract: The management of early-stage breast cancer in older patients is complex and requires a careful balance of the risk of cancer death with the competing risks of comorbidities and treatment-related toxicity in women with largely favorable disease. As the US population continues to age, oncologists will increasingly encounter this clinical challenge. Several strategies involving each core component of breast cancer therapy have been investigated to minimize treatment in these patients while still maintaining acceptable outcomes. These include omission of primary tumor resection, surgical axillary evaluation, systemic chemotherapy, and/or radiotherapy, as well as reduction in radiotherapy treatment volume (partial breast irradiation) or total treatment time (hypofractionation). We review these strategies and the literature supporting their use, as well as future directions for treatment minimization.